Difunctional water electrolysis catalytic electrode taking carbonized wood as substrate as well as preparation method and application of difunctional water electrolysis catalytic electrode
By loading the iron-nickel-molybdenum phosphide mixture on three-dimensional porous carbide wood, a dual-function electrolytic catalytic electrode is solved, and the existing electrolytic catalytic electrode materials are achieved is achieved with high efficiency and low cost. Hydrogen production technology by electrolyzing water.
Patent Information
- Application Number
- CN202411364020.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing electrolytic water catalytic electrode materials are expensive and have poor stability, which limits the large-scale commercial application of electrolytic water hydrogen production technology, especially the poor catalytic effect of HER and OER.
Three-dimensional porous carbide wood is used as the substrate, and the iron-nickel-molybdenum phosphide mixture is loaded through hydrothermal reaction and vapor-phase phosphating method to form a dual-function electrolytic catalytic electrode, simplifying the preparation process and reducing costs.
It achieves efficient HER and OER electrocatalytic performance and stability, reduces the cost of hydrogen production, and is suitable for large-scale production applications.
Smart Images

Figure CN119221014A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water electrolysis catalytic electrodes, and in particular to a bifunctional water electrolysis catalytic electrode based on carbonized wood, and a preparation method and application thereof. Background Art
[0002] With the continuous growth of the global population and the rapid development of the world economy, people's demand for energy has risen sharply. Therefore, the global energy crisis and environmental problems caused by the consumption of non-renewable energy such as oil and coal are becoming increasingly serious. At present, hydrogen energy as an environmentally friendly and recyclable energy source has attracted global attention. Water electrolysis technology is the main way to produce green hydrogen. It has the characteristics of cleanliness, pollution-free and high product purity. It has been considered to be the most promising hydrogen production technology. This technology includes anode oxygen evolution reaction and cathode hydrogen evolution reaction. The traditional catalytic electrodes used are mainly precious metals, but their low reserves, high cost and poor stability limit their large-scale commercial application. Therefore, it is of great significance to research and develop catalytic electrodes for water electrolysis that are rich in resources, low in price and high in catalytic activity.
[0003] At present, in the field of water electrolysis for hydrogen production, the most commonly used substrates are expensive materials such as nickel foam, copper foam, carbon cloth, and carbon paper. Wood is a very promising natural organic composite material with a well-defined structure, complex and orderly structure, anisotropy, low density, and excellent mechanical properties. After high-temperature carbonization, it can still maintain its original structure, providing an excellent platform for the loading of catalytic materials. Combining it with electrocatalytic materials can greatly improve the efficiency and performance of water electrolysis.
[0004] Among a series of transition metal elements, nickel and iron have large reserves in nature, and the unique synergistic effect and electronic structure between the elements can provide a large number of active sites for the combined materials, improving the redox properties of the materials. Therefore, nickel-iron-based materials have become one of the most efficient catalytic electrodes for OER. At the same time, molybdenum phosphide is widely used in HER catalysis due to its low cost and high catalytic activity. However, the lack of active sites and poor conductivity increase the complexity of their design and preparation, resulting in poor catalytic effect in water electrolysis.
[0005] Based on this, this application proposes a bifunctional water electrolysis catalytic electrode for HER and OER with three-dimensional porous carbonized wood as the substrate and the synergy of nickel, iron and molybdenum atoms, so as to reduce the cost of hydrogen production and improve the efficiency of hydrogen production. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and propose a bifunctional water electrolysis catalytic electrode based on carbonized wood and its preparation method and application. The prepared bifunctional water electrolysis catalytic electrode has excellent HER and OER electrocatalytic performance and stability, and the preparation method is simple, efficient, low-cost, and suitable for large-scale production and application.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A bifunctional water electrolysis catalytic electrode based on carbonized wood, comprising active components of metal A, metal B, metal C and non-metal D loaded on its skeleton;
[0009] The active component includes a mixture of metal A, metal B, metal C and non-metal D grown in coordination;
[0010] The metal A, metal B and metal C are all transition metals.
[0011] Preferably, the metal A, metal B and metal C are independently at least one of iron, nickel, molybdenum, copper and chromium, and are different elements; the non-metal D is any one of phosphorus, sulfur and carbon.
[0012] Preferably, the metal A is iron, the metal B is nickel, the metal C is molybdenum, and the non-metal D is phosphorus; the active ingredient is in the form of a metal layer, and the preferred active ingredient here can further synergistically improve the HER and OER performances of the material.
[0013] Another object of the present invention is to provide a method for preparing a bifunctional water electrolysis catalytic electrode based on carbonized wood, comprising the following steps:
[0014] Step 1, pre-treating the wood chips and calcining them at high temperature to obtain carbonized wood chips;
[0015] Step 2, growing a metal layer on the carbonized wood chip through a hydrothermal reaction;
[0016] Step 3: Perform high-temperature gas-phase phosphating on the sample under the protection of an inert gas, and finally obtain a catalytic electrode loaded with iron-nickel-molybdenum phosphide.
[0017] Preferably, in step 1, the wood chips are beech or basswood; pretreatment includes pickling and water washing; high-temperature calcination is carried out in a tubular furnace, the initial calcination temperature is 400-600°C, the initial calcination time is 1-2h, and then the temperature is raised to 800-1100°C, and the calcination time is 2-4h.
[0018] Preferably, in step 2, the temperature of the hydrothermal reaction is 120-180° C. and the time is 12-24 h;
[0019] The mixed solution for the hydrothermal reaction includes a metal A source, a metal B source and a metal C source, and the molar ratio of the metal A source, the metal B source and the metal C source is (1-1.34): (1-1.94): (2-3.5), and then the pH value is adjusted to 7 using sodium citrate dihydrate;
[0020] The metal A source is at least one of ferric chloride hexahydrate and ferric nitrate nonahydrate, the metal B source is at least one of nickel chloride hexahydrate and nickel nitrate hexahydrate, the metal C source is at least one of sodium molybdate dihydrate and ammonium molybdate tetrahydrate, and the non-metal D source is sodium hypophosphite.
[0021] Preferably, in step 3, the high-temperature gas phase phosphating is carried out in a tubular furnace, the heating rate is controlled to be 2-5°C / min, the reaction temperature is 300-450°C, and the reaction time is 1-2h.
[0022] The present invention also provides an application of a bifunctional water electrolysis catalytic electrode with carbonized wood as a substrate prepared by the above-mentioned preparation method as a catalytic electrode for HER and OER. Specifically, the bifunctional water electrolysis catalytic electrode with carbonized wood as a substrate is used as a catalytic electrode for HER and OER to catalyze the electrolysis of aqueous solution, has high catalytic activity and stability, and effectively reduces the cost of hydrogen production.
[0023] The aqueous solution is an alkaline aqueous solution, the solute is any one of potassium hydroxide or sodium hydroxide, and the molar concentration of the solute in the alkaline aqueous solution is 1-2M.
[0024] The present invention also provides an application of the bifunctional water electrolysis catalytic electrode with carbonized wood as the substrate prepared by the above-mentioned preparation method as a working electrode for electrochemical testing, specifically, using the bifunctional water electrolysis catalytic electrode with carbonized wood as the substrate as the working electrode for electrochemical testing.
[0025] Among them, the electrochemical test conditions are: according to the conventional three-electrode system, with graphite rod as the counter electrode and Hg / HgO as the reference electrode, the HER and OER activities of the bifunctional water electrolysis catalytic electrode based on carbonized wood were tested in a single electrolytic cell.
[0026] A hydrogen production electrode is a bifunctional water electrolysis catalytic electrode with carbonized wood as a substrate, which is prepared by the above preparation method.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The present invention uses three-dimensional porous carbonized wood as a substrate and loads active ingredients on the substrate, wherein the active ingredients are iron nickel molybdenum phosphide. The bifunctional water electrolysis catalytic electrode based on carbonized wood prepared by the present invention can give the material good HER and OER dual functions.
[0029] 2. The preparation process of the present invention is simple and the reaction conditions are mild. The catalytic electrode is grown on a three-dimensional porous carbonized wood substrate without the need to add an adhesive. The catalytic material is tightly combined with the conductive substrate, providing an effective idea for developing a low-cost, high-activity bifunctional water electrolysis catalytic electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the process of the preparation method of the present invention;
[0031] Figure 2 This is a SEM image of the bifunctional water electrolysis catalytic electrode based on carbonized wood prepared in Example 1 of the present invention at 1 μm;
[0032] Figure 3 This is a SEM image of the bifunctional water electrolysis catalytic electrode based on carbonized wood prepared in Example 1 of the present invention at 2 μm;
[0033] Figure 4 This is a SEM image of the bifunctional water electrolysis catalytic electrode based on carbonized wood prepared in Comparative Example 1 of the present invention at 2 μm;
[0034] Figure 5 This is a SEM image of the bifunctional water electrolysis catalytic electrode based on carbonized wood prepared in Comparative Example 1 of the present invention at 10 μm;
[0035] Figure 6 The linear sweep voltammetric curves of the oxygen evolution reaction of the bifunctional water electrolysis catalytic electrode based on carbonized wood prepared in Example 1 of the present invention and Comparative Examples 1-3;
[0036] Figure 7 The linear sweep voltammetric curves of the hydrogen evolution reaction of the bifunctional water electrolysis catalytic electrode based on carbonized wood prepared in Example 1 of the present invention and Comparative Examples 1-3 are shown. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings, so that those skilled in the art can better understand the advantages and features of the present invention, thereby making a clearer definition of the protection scope of the present invention. The embodiments described in the present invention are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0038] Embodiment 1:
[0039] A bifunctional water electrolysis catalytic electrode based on carbonized wood is provided, wherein nickel-iron-molybdenum phosphide mixture particles are produced by hydrothermal reaction and gas phase phosphating and loaded on the carbonized wood skeleton.
[0040] The method for preparing the bifunctional water electrolysis catalytic electrode based on carbonized wood comprises the following steps:
[0041] (1) Cut wood chips into 25*20*2 mm pieces and ultrasonically wash them several times with 1M dilute hydrochloric acid, deionized water and anhydrous ethanol until they are clean;
[0042] (2) Place the wood chips in a ceramic boat and move it to a tube furnace. Under argon protection, heat the temperature to 500°C at a rate of 2°C / min and keep it for 1 h. Then, heat the temperature to 900°C at a rate of 5°C / min and keep it for 2 h.
[0043] (3) preparing a mixed solution containing 1 mmol of ferric chloride hexahydrate (metal A source), 1.28 mmol of nickel chloride hexahydrate (metal B source), 0.256 mmol of sodium molybdate tetrahydrate (metal C source) and 30 mL of deionized water, adjusting the pH value of the solution to 7 using sodium citrate dihydrate, immersing the carbonized wood chips in step (2) in the above solution, placing the carbonized wood chips in a high-pressure reactor for hydrothermal reaction, maintaining the temperature at 180° C., and the reaction time for 12 h;
[0044] (4) taking out the wood chips from step (3) and placing them in a vacuum drying oven at a drying temperature of 60° C. for 12 h;
[0045] (5) The dried wood chips in step (4) were taken out and placed in the middle of a tube furnace. A ceramic boat containing 1.2 g of sodium hypophosphite powder (non-metallic D source) was placed upstream. Under argon protection, the temperature was raised to 300° C. at a rate of 2° C. / min, kept at this temperature for 2 h, and then naturally cooled to room temperature.
[0046] (6) taking out the calcined wood chips from step (5), and washing them with deionized water and anhydrous ethanol until they are clean;
[0047] (7) The wood chips of step (6) are placed in a vacuum drying oven at a drying temperature of 60° C. for 12 h, and then the bifunctional water electrolysis catalytic electrode based on carbonized wood in this embodiment is obtained.
[0048] The bifunctional water electrolysis catalytic electrode based on carbonized wood in this embodiment was directly used as a working electrode and immersed in a 1M KOH solution to perform linear sweep voltammetry tests of hydrogen and oxygen evolution to characterize its electrocatalytic activity for hydrogen and oxygen evolution reactions. Figure 2 and Figure 3 As shown, at 10 mA cm -2 At a current density of , the overpotential for hydrogen evolution is only 96 mV and the overpotential for oxygen evolution is 210 mV, showing excellent electrocatalytic activity.
[0049] Embodiment 2:
[0050] A bifunctional water electrolysis catalytic electrode based on carbonized wood is provided, wherein nickel-iron-molybdenum phosphide mixture particles are produced by hydrothermal reaction and gas phase phosphating and loaded on the carbonized wood skeleton.
[0051] The method for preparing the bifunctional water electrolysis catalytic electrode based on carbonized wood comprises the following steps:
[0052] (1) Cut wood chips into 25*20*2 mm pieces and ultrasonically wash them several times with 1M dilute hydrochloric acid, deionized water and anhydrous ethanol until they are clean;
[0053] (2) Place the wood chips in a ceramic boat and move it to a tube furnace. Under argon protection, heat the temperature to 500°C at a rate of 2°C / min and keep it for 1 h. Then, heat the temperature to 900°C at a rate of 5°C / min and keep it for 2 h.
[0054] (3) preparing a mixed solution containing 1 mmol of ferric chloride hexahydrate, 1 mmol of nickel chloride hexahydrate, 2 mmol of sodium molybdate tetrahydrate and 30 mL of deionized water, adjusting the pH value of the solution to 7 using sodium citrate dihydrate, immersing the wood chips in step (2) in the above solution, placing the mixture in a high-pressure reactor for hydrothermal reaction, maintaining the temperature at 180° C., and reacting for 12 h;
[0055] (4) taking out the impregnated wood chips from step (3) and placing them in a vacuum drying oven at a drying temperature of 60° C. for 12 h;
[0056] (5) The dried wood chips in step (4) were taken out and placed in the middle of a tube furnace, with a ceramic boat containing 1.2 g of sodium hypophosphite powder placed upstream. Under argon protection, the temperature was raised to 300° C. at a rate of 2° C. / min, kept at that temperature for 2 h, and then naturally cooled to room temperature;
[0057] (6) taking out the calcined wood chips from step (5), and washing them with deionized water and anhydrous ethanol until they are clean;
[0058] (7) The wood chips of step (6) are placed in a vacuum drying oven at a drying temperature of 60° C. for 12 h, and then the bifunctional water electrolysis catalytic electrode based on carbonized wood in this embodiment is obtained.
[0059] The bifunctional water electrolysis catalytic electrode based on carbonized wood in this example was directly used as a working electrode and immersed in a 1M KOH solution to perform linear sweep voltammetry tests of hydrogen and oxygen evolution to characterize its electrocatalytic activity for hydrogen and oxygen evolution reactions. -2 At a current density of , the overpotential for hydrogen evolution is only 112 mV, and the overpotential for oxygen evolution is 257.5 mV, showing excellent electrocatalytic activity.
[0060] Embodiment 3:
[0061] A bifunctional water electrolysis catalytic electrode based on carbonized wood is provided, in which nickel-iron-molybdenum phosphide mixture particles are produced by hydrothermal reaction and gas phase phosphating and loaded on the carbonized wood skeleton.
[0062] The method for preparing the bifunctional water electrolysis catalytic electrode based on carbonized wood comprises the following steps:
[0063] (1) Cut wood chips into 25*20*2 mm pieces and ultrasonically wash them several times with 1M dilute hydrochloric acid, deionized water and anhydrous ethanol until they are clean;
[0064] (2) Place the wood chips in a ceramic boat and move it to a tube furnace. Under argon protection, heat the temperature to 500°C at a rate of 2°C / min and keep it for 1 h. Then, heat the temperature to 900°C at a rate of 5°C / min and keep it for 2 h.
[0065] (3) preparing a mixed solution containing 1 mmol nickel chloride hexahydrate, 1.34 mmol ferric chloride hexahydrate, 2.18 mmol sodium molybdate tetrahydrate and 30 mL deionized water, adjusting the pH value of the solution to 7 using sodium citrate dihydrate, immersing the wood chips in step (2) in the above solution, placing the mixture in a high-pressure reactor for hydrothermal reaction, maintaining the temperature at 180° C., and reacting for 12 h;
[0066] (4) taking out the wood chips from step (3) and placing them in a vacuum drying oven at a drying temperature of 60° C. for 12 h;
[0067] (5) The dried wood chips in step (4) were taken out and placed in the middle of a tube furnace, with a ceramic boat containing 1.2 g of sodium hypophosphite powder placed upstream. Under argon protection, the temperature was raised to 300° C. at a rate of 2° C. / min, kept at that temperature for 2 h, and then naturally cooled to room temperature;
[0068] (6) taking out the calcined wood chips from step (5), and washing them with deionized water and anhydrous ethanol until they are clean;
[0069] (7) The wood chips of step (6) are placed in a vacuum drying oven at a drying temperature of 60° C. for 12 h, and then the bifunctional water electrolysis catalytic electrode based on carbonized wood in this embodiment is obtained.
[0070] The bifunctional water electrolysis catalytic electrode based on carbonized wood in this example was directly used as a working electrode and immersed in a 1M KOH solution to perform linear sweep voltammetry tests of hydrogen and oxygen evolution to characterize its electrocatalytic activity for hydrogen and oxygen evolution reactions. -2 At a current density of , the overpotential for hydrogen evolution is 82 mV and the overpotential for oxygen evolution is 268.5 mV, showing excellent electrocatalytic activity.
[0071] Embodiment 4:
[0072] A bifunctional water electrolysis catalytic electrode based on carbonized wood is provided, wherein nickel-iron-molybdenum phosphide mixture particles are produced by hydrothermal reaction and gas phase phosphating and loaded on the carbonized wood skeleton.
[0073] The method for preparing the bifunctional water electrolysis catalytic electrode based on carbonized wood comprises the following steps:
[0074] (1) Cut wood chips into 25*20*2 mm pieces and ultrasonically wash them several times with 1M dilute hydrochloric acid, deionized water and anhydrous ethanol until they are clean;
[0075] (2) Place the wood chips in a crucible and move it to a tube furnace. Under argon protection, heat the temperature to 500°C at a rate of 2°C / min and keep it for 1 h. Then, heat the temperature to 900°C at a rate of 5°C / min and keep it for 2 h.
[0076] (3) immersing the wood chips of step (2) in a mixed solution containing 1 mmol of ferric chloride hexahydrate, 1.72 mmol of nickel chloride hexahydrate, 3.33 mmol of sodium molybdate tetrahydrate and 30 mL of deionized water, adjusting the pH value of the solution to 7 using sodium citrate dihydrate, immersing the wood chips of step (2) in the above solution, placing the solution in a high-pressure reactor for hydrothermal reaction, maintaining the temperature at 180° C., and the reaction time for 12 h;
[0077] (4) taking out the wood chips from step (3) and placing them in a vacuum drying oven at a drying temperature of 60° C. for 12 h;
[0078] (5) The dried wood chips in step (4) were taken out and placed in the middle of a tube furnace, with a ceramic boat containing 1.2 g of sodium hypophosphite powder placed upstream. Under argon protection, the temperature was raised to 300° C. at a rate of 2° C. / min, kept at that temperature for 2 h, and then naturally cooled to room temperature;
[0079] (6) taking out the calcined wood chips from step (5), and washing them with deionized water and anhydrous ethanol until they are clean;
[0080] (7) The wood chips of step (6) are placed in a vacuum drying oven at a drying temperature of 60° C. for 12 h, and then the bifunctional water electrolysis catalytic electrode based on carbonized wood in this embodiment is obtained.
[0081] The bifunctional water electrolysis catalytic electrode based on carbonized wood in this example was directly used as a working electrode and immersed in a 1M KOH solution to perform linear sweep voltammetry tests of hydrogen and oxygen evolution to characterize its electrocatalytic activity for hydrogen and oxygen evolution reactions. -2 At a current density of , the overpotential for hydrogen evolution is 128 mV and the overpotential for oxygen evolution is 296.5 mV.
[0082] Embodiment 5:
[0083] A bifunctional water electrolysis catalytic electrode based on carbonized wood is provided, in which nickel-iron-molybdenum phosphide mixture particles are produced by hydrothermal reaction and gas phase phosphating and loaded on the carbonized wood skeleton.
[0084] The method for preparing the bifunctional water electrolysis catalytic electrode based on carbonized wood comprises the following steps:
[0085] (1) Cut wood chips into 25*20*2 mm pieces and ultrasonically wash them several times with 1M dilute hydrochloric acid, deionized water and anhydrous ethanol until they are clean;
[0086] (2) Place the wood chips in a ceramic boat and move it to a tube furnace. Under argon protection, heat the temperature to 500°C at a rate of 2°C / min and keep it for 1 h. Then, heat the temperature to 900°C at a rate of 5°C / min and keep it for 2 h.
[0087] (3) preparing a mixed solution containing 1 mmol of ferric chloride hexahydrate, 3 mmol of nickel chloride hexahydrate, 0.6 mmol of sodium molybdate tetrahydrate and 30 mL of deionized water, adjusting the pH value of the solution to 7 using sodium citrate dihydrate, immersing the wood chips in step (2) in the above solution, placing the mixture in a high-pressure reactor for hydrothermal reaction, maintaining the temperature at 180° C., and reacting for 12 h;
[0088] (4) taking out the wood chips from step (3) and placing them in a vacuum drying oven at a drying temperature of 60° C. for 12 h;
[0089] (5) taking out the dried wood chips from step (4), placing them in the middle of a tube furnace, placing a ceramic boat containing 1.2 g of sodium hypophosphite powder upstream, and heating the wood chips to 300° C. at a heating rate of 2° C. / min under argon protection, keeping the temperature for 2 h, then heating the wood chips to 900° C. at a heating rate of 5° C. / min for calcination, keeping the temperature for 1 h, and then cooling the wood chips naturally to room temperature;
[0090] (6) taking out the calcined wood chips from step (5), and washing them with deionized water and anhydrous ethanol until they are clean;
[0091] (7) The wood chips of step (6) are placed in a vacuum drying oven at a drying temperature of 60° C. for 12 h, and then the bifunctional water electrolysis catalytic electrode based on carbonized wood in this embodiment is obtained.
[0092] The bifunctional water electrolysis catalytic electrode based on carbonized wood in this example was directly used as a working electrode and immersed in a 1M KOH solution to perform linear sweep voltammetry tests of hydrogen and oxygen evolution to characterize its electrocatalytic activity for hydrogen and oxygen evolution reactions. -2At a current density of , the overpotential for hydrogen evolution is 295.5 mV and the overpotential for oxygen evolution is 268.5 mV.
[0093] Embodiment 6:
[0094] A bifunctional water electrolysis catalytic electrode based on carbonized wood is provided, in which nickel-iron-molybdenum phosphide mixture particles are produced by hydrothermal reaction and gas phase phosphating and loaded on the carbonized wood skeleton.
[0095] The method for preparing the bifunctional water electrolysis catalytic electrode based on carbonized wood comprises the following steps:
[0096] (1) Cut wood chips into 25*20*2 mm pieces and ultrasonically wash them several times with 1M dilute hydrochloric acid, deionized water and anhydrous ethanol until they are clean;
[0097] (2) Place the wood chips in a ceramic boat and move it to a tube furnace. Under argon protection, heat the temperature to 500°C at a rate of 2°C / min and keep it for 1 h. Then, heat the temperature to 900°C at a rate of 5°C / min and keep it for 2 h.
[0098] (3) preparing a mixed solution containing 1 mmol of ferric chloride hexahydrate, 3 mmol of nickel chloride hexahydrate, 1.2 mmol of sodium molybdate tetrahydrate and 30 mL of deionized water, adjusting the pH value of the solution to 7 using sodium citrate dihydrate, immersing the wood chips in step (2) in the above solution, placing the mixture in a high-pressure reactor for hydrothermal reaction, maintaining the temperature at 180° C., and reacting for 12 h;
[0099] (4) taking out the wood chips from step (3) and placing them in a vacuum drying oven at a drying temperature of 60° C. for 12 h;
[0100] (5) The dried wood chips in step (4) were taken out and placed in the middle of a tube furnace, with a ceramic boat containing 1.2 g of sodium hypophosphite powder placed upstream. Under argon protection, the temperature was raised to 300° C. at a rate of 2° C. / min, kept at that temperature for 2 h, and then naturally cooled to room temperature;
[0101] (6) taking out the calcined wood chips from step (5), and washing them with deionized water and anhydrous ethanol until they are clean;
[0102] (7) The wood chips of step (6) are placed in a vacuum drying oven at a drying temperature of 60° C. for 12 h, and then the bifunctional water electrolysis catalytic electrode based on carbonized wood in this embodiment is obtained.
[0103] The bifunctional water electrolysis catalytic electrode based on carbonized wood in this example was directly used as a working electrode and immersed in a 1M KOH solution to perform linear sweep voltammetry tests of hydrogen and oxygen evolution to characterize its electrocatalytic activity for hydrogen and oxygen evolution reactions. -2At a current density of , the overpotential for hydrogen evolution is 187 mV and the overpotential for oxygen evolution is 297 mV.
[0104] Embodiment 7:
[0105] A bifunctional water electrolysis catalytic electrode based on carbonized wood is provided, in which nickel-iron-molybdenum phosphide mixture particles are produced by hydrothermal reaction and gas phase phosphating and loaded on the carbonized wood skeleton.
[0106] The method for preparing the bifunctional water electrolysis catalytic electrode based on carbonized wood comprises the following steps:
[0107] (1) Cut wood chips into 25*20*2 mm pieces and ultrasonically wash them several times with 1M dilute hydrochloric acid, deionized water and anhydrous ethanol until they are clean;
[0108] (2) Place the wood chips in a crucible and move it to a tube furnace. Under argon protection, heat the temperature to 500°C at a rate of 2°C / min and keep it for 1 h. Then, heat the temperature to 900°C at a rate of 5°C / min and keep it for 2 h.
[0109] (3) immersing the beech wood pieces obtained in step (2) in a mixed solution containing 1 mmol of ferric chloride hexahydrate, 3 mmol of nickel chloride hexahydrate, 1.5 mmol of sodium molybdate tetrahydrate and 30 mL of deionized water, adjusting the pH value of the solution to 7 using sodium citrate dihydrate, and placing the solution in a high-pressure reactor for hydrothermal reaction, maintaining the temperature at 180° C. for a reaction time of 12 h;
[0110] (4) taking out the wood chips from step (3) and placing them in a vacuum drying oven at a drying temperature of 60° C. for 12 h;
[0111] (5) The dried wood chips in step (4) were taken out and placed in the middle of a tube furnace, with a ceramic boat containing 1.2 g of sodium hypophosphite powder placed upstream. Under argon protection, the temperature was raised to 300° C. at a rate of 2° C. / min, kept at that temperature for 2 h, and then naturally cooled to room temperature;
[0112] (6) taking out the calcined wood chips from step (5), and washing them with deionized water and anhydrous ethanol until they are clean;
[0113] (7) The wood chips of step (6) are placed in a vacuum drying oven at a drying temperature of 60° C. for 12 h, and then the bifunctional water electrolysis catalytic electrode based on carbonized wood in this embodiment is obtained.
[0114] The bifunctional water electrolysis catalytic electrode based on carbonized wood in this example was directly used as a working electrode and immersed in a 1M KOH solution to perform linear sweep voltammetry tests of hydrogen and oxygen evolution to characterize its electrocatalytic activity for hydrogen and oxygen evolution reactions. -2At a current density of , the overpotential for hydrogen evolution is 194 mV and the overpotential for oxygen evolution is 272 mV.
[0115] Comparative Example 1:
[0116] The main difference between this comparative example and Example 1 is that the NiFeMo composite material is first prepared by vacuum solution impregnation method, and then vapor phase phosphating is performed.
[0117] The preparation method of this comparative example comprises the following steps:
[0118] (1) Cut wood chips into 25*20*2 mm pieces, and use 1M dilute hydrochloric acid, deionized water and anhydrous ethanol to ultrasonically wash them several times until they are clean. Then put them into a vacuum drying oven and set the drying temperature to 60°C for 12 h.
[0119] (2) preparing a mixed solution of 1 mmol ferric chloride hexahydrate, 1.28 mmol nickel chloride hexahydrate, 0.256 mmol sodium molybdate tetrahydrate and 30 mL deionized water, adding sodium citrate dihydrate to adjust the pH of the solution to 7, immersing the wood chips in step (1), transferring to a vacuum environment for immersion, and immersing for 12 h;
[0120] (3) taking out the impregnated wood chips from step (2) and placing them in a vacuum drying oven at a drying temperature of 60° C. for 12 h;
[0121] (4) The impregnated wood chips after drying in step (3) are taken out and placed in the middle section of a tubular furnace. A ceramic boat containing 1.2 g of sodium hypophosphite powder is placed upstream. The wood chips are placed in a crucible and moved to the tubular furnace. Under argon protection, the temperature is raised to 300° C. at a rate of 2° C. / min and kept for 2 h, then raised to 900° C. and kept for 6 h.
[0122] (5) taking out the wood chips from step (4) and rinsing them with deionized water and anhydrous ethanol until they are clean;
[0123] (6) Then, a bifunctional water electrolysis catalytic electrode based on carbonized wood was obtained in this comparative example.
[0124] The bifunctional water electrolysis catalytic electrode based on carbonized wood in this embodiment was directly used as a working electrode and immersed in a 1M KOH solution to perform linear sweep voltammetry tests of hydrogen and oxygen evolution to characterize its electrocatalytic activity for hydrogen and oxygen evolution reactions. Figure 2 and Figure 3 As shown, at 10 mA cm -2 At a current density of , the overpotential for hydrogen evolution is 227.5 mV and the overpotential for oxygen evolution is 308.5 mV.
[0125] Comparative Example 2:
[0126] The difference between this comparative example and Example 1 is that the NiFe material is first prepared by vacuum solution impregnation method, and then the NiFe-MoP material is prepared by solution impregnation.
[0127] The preparation method of this comparative example comprises the following steps:
[0128] (1) Cut wood chips into 25*20*2 mm pieces and ultrasonically wash them several times with 1M dilute hydrochloric acid, deionized water and anhydrous ethanol until they are clean;
[0129] (2) Weigh 1 mmol of ferric chloride hexahydrate and 1.28 mmol of nickel chloride hexahydrate, add 30 mL of deionized water to prepare a mixed solution, immerse the wood chips in step (1) in the mixed solution, and transfer to a vacuum environment for immersion for 12 hours;
[0130] (3) taking out the impregnated wood chips from step (2) and placing them in a vacuum drying oven at a drying temperature of 60° C. for 6 h;
[0131] (4) Weigh 0.256 mmol of sodium molybdate tetrahydrate and 0.2 mmol of sodium hypophosphite, add 30 mL of deionized water to form a mixed solution, and immerse the dried wood chips in step (3) for 12 hours at room temperature;
[0132] (5) taking out the impregnated wood chips from step (4) and placing them in a vacuum drying oven at a drying temperature of 60° C. for 6 h;
[0133] (6) taking out the impregnated wood chips dried in step (5), placing them in the middle of a tube furnace, and calcining them at a rate of 5°C / min to 900°C under argon protection, keeping the temperature for 3 hours, and then cooling them naturally to room temperature;
[0134] (7) taking out the calcined wood chips from step (6) and washing them with deionized water and anhydrous ethanol until they are clean;
[0135] (8) The wood chips of step (7) are placed in a vacuum drying oven at a drying temperature of 60° C. for 12 h, thereby obtaining a bifunctional water electrolysis catalytic electrode based on carbonized wood in this comparative example.
[0136] The bifunctional water electrolysis catalytic electrode based on carbonized wood in this embodiment was directly used as a working electrode and immersed in a 1M KOH solution to perform linear sweep voltammetry tests of hydrogen and oxygen evolution to characterize its electrocatalytic activity for hydrogen and oxygen evolution reactions. Figure 2 and Figure 3 As shown, at 10 mA cm -2 At a current density of , the overpotential for hydrogen evolution is 182 mV and the overpotential for oxygen evolution is 235 mV.
[0137] Comparative Example 3:
[0138] The difference between this comparative example and Example 1 is that the hydrothermal reaction is performed first and then the wood carbonization is performed.
[0139] The preparation method of this comparative example comprises the following steps:
[0140] (1) Cut wood chips into 25*20*2 mm pieces, and use 1M dilute hydrochloric acid, deionized water and anhydrous ethanol to ultrasonically wash them several times until they are clean. Then put them into a vacuum drying oven and set the drying temperature to 60°C for 12 h.
[0141] (2) preparing a mixed solution of 1 mmol ferric chloride hexahydrate, 1.28 mmol nickel chloride hexahydrate, 0.256 mmol sodium molybdate tetrahydrate and 30 mL deionized water, adding sodium citrate dihydrate to adjust the pH of the solution to 7, immersing the wood chips in step (1), and transferring to a high-pressure reactor for hydrothermal reaction for 12 h;
[0142] (3) taking out the wood chips from step (2) and placing them in a vacuum drying oven at a drying temperature of 60° C. for 12 h;
[0143] (4) Take out the wood chips dried in step (3) and place them in the middle of a tubular furnace. Place a ceramic boat containing 1.2 g of sodium hypophosphite powder upstream. Place the wood chips in a crucible and move them to the tubular furnace. Under argon protection, raise the temperature to 400°C at a rate of 2°C / min and keep it for 2 hours. Then raise the temperature to 900°C and keep it for 2 hours.
[0144] (5) taking out the wood chips from step (4) and rinsing them with deionized water and anhydrous ethanol until they are clean;
[0145] (6) Then, a bifunctional water electrolysis catalytic electrode based on carbonized wood was obtained in this comparative example.
[0146] The bifunctional water electrolysis catalytic electrode based on carbonized wood in this embodiment was directly used as a working electrode and immersed in a 1M KOH solution to perform linear sweep voltammetry tests of hydrogen and oxygen evolution to characterize its electrocatalytic activity for hydrogen and oxygen evolution reactions. Figure 2 and Figure 3 As shown, at 10 mA cm -2 At a current density of , the overpotential for hydrogen evolution is 178 mV and the overpotential for oxygen evolution is 276 mV.
[0147] In summary, the bifunctional water electrolysis catalytic electrode prepared by the present invention has excellent HER and OER electrocatalytic performance and stability, and the preparation method is simple, efficient, and low-cost, and is suitable for large-scale production applications.
[0148] The description and practice disclosed in the present invention are easy to think and understand for ordinary technicians in the technical field, and several improvements and modifications can be made without departing from the principles of the present invention. Therefore, modifications or improvements made without departing from the spirit of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A bifunctional water electrolysis catalytic electrode based on carbonized wood, characterized in that: The active ingredients include metal A, metal B, metal C and non-metal D loaded on its skeleton; The active component includes a mixture of metal A, metal B, metal C and non-metal D grown in coordination; The metal A, metal B and metal C are all transition metals.
2. The bifunctional water electrolysis catalytic electrode based on carbonized wood according to claim 1, characterized in that: The metal A, metal B and metal C are independently at least one of iron, nickel, molybdenum, copper and chromium, and are different elements; the non-metal D is any one of phosphorus, sulfur and carbon.
3. The bifunctional water electrolysis catalytic electrode based on carbonized wood according to claim 2, characterized in that: The metal A is iron, the metal B is nickel, the metal C is molybdenum, and the non-metal D is phosphorus; the active ingredient is in the form of a metal layer.
4. The method for preparing a bifunctional water electrolysis catalytic electrode based on carbonized wood according to claim 1, characterized in that: The following steps are involved: Step 1, pre-treating the wood chips and calcining them at high temperature to obtain carbonized wood chips; Step 2, growing a metal layer on the carbonized wood chip through a hydrothermal reaction; Step 3: Perform high-temperature gas-phase phosphating on the sample under the protection of an inert gas, and finally obtain a catalytic electrode loaded with iron-nickel-molybdenum phosphide.
5. The method for preparing a bifunctional water electrolysis catalytic electrode based on carbonized wood according to claim 4, characterized in that: In step 1, the wood chips are beech or basswood; the pretreatment includes pickling and washing; High temperature calcination is carried out in a tubular furnace, with an initial calcination temperature of 400-600°C and an initial calcination time of 1-2h, followed by a temperature increase to 800-1100°C and a calcination time of 2-4h.
6. The method for preparing a bifunctional water electrolysis catalytic electrode based on carbonized wood according to claim 4, characterized in that: In step 2, the temperature of the hydrothermal reaction is 120-180°C and the time is 12-24h; The mixed solution for the hydrothermal reaction includes a metal A source, a metal B source and a metal C source, and the molar ratio of the metal A source, the metal B source and the metal C source is (1-1.34): (1-1.94): (2-3.5), and then the pH value is adjusted to 7 using sodium citrate dihydrate; The metal A source is at least one of ferric chloride hexahydrate and ferric nitrate nonahydrate, the metal B source is at least one of nickel chloride hexahydrate and nickel nitrate hexahydrate, the metal C source is at least one of sodium molybdate dihydrate and ammonium molybdate tetrahydrate, and the non-metal D source is sodium hypophosphite.
7. The method for preparing a bifunctional water electrolysis catalytic electrode based on carbonized wood according to claim 4, characterized in that: In step 3, the high-temperature gas phase phosphating is carried out in a tubular furnace, the heating rate is controlled to be 2-5°C / min, the reaction temperature is 300-450°C, and the reaction time is 1-2h.
8. Use of a bifunctional water electrolysis catalytic electrode based on carbonized wood, prepared by the preparation method described in any one of claims 4 to 7, as a catalytic electrode for HER and OER.
9. Use of a bifunctional water electrolysis catalytic electrode based on carbonized wood, prepared by the preparation method according to any one of claims 4 to 7, as a working electrode for electrochemical testing.
10. A hydrogen production electrode, characterized in that: A bifunctional water electrolysis catalytic electrode based on carbonized wood, prepared by the preparation method described in any one of claims 4 to 7.
Citation Information
Cited By
Dopamine electrochemical sensor based on carbonized wood natural structure as well as preparation method and application of dopamine electrochemical sensor
CN120668749A